Kadar Asam Urat pada Perempuan Menopause - Safira Zahro; Umi Rosidah (Jaringan Laboratorium Medis, 2021)
Based on data from Riskesdas 2013, in line with increasing age the prevalence of joint disease has increased. The trigger is abnormal metabolic processes in the body and 10% of cases occur in postmenopausal women because the production of the hormone estrogen is disrupted. If treatment is not carried out, it will result in chronic gouty arthritis, resulting in paralysis. The purpose of this study was to determine the description of uric acid levels in postmenopausal women in Berahan Kulon Village, Wedung District, Demak Regency. The research method used is an observational study with a cross sectional approach. Of the 20 research subjects, 1 research subject had low uric acid levels, 9 research subjects had normal uric acid levels, and 10 research subjects had high uric acid levels. High uric acid levels were dominated by the age group 51-55 years, menopause duration 6-10 years and > 10 years, no history of heredity, and consumption of foods high in uric acid 3-5 times/week and > 5 times/week. The conclusion of this study is that 5% of postmenopausal women have low uric acid levels, 45% have normal uric acid levels, and 50% have high uric acid levels.